Compression properties of metal beetle elytron plates and the elementary unit of the trabecular-honeycomb core structure. (September 2019) - Zhang, Xiaoming; Chen, Jinxiang; Okabe, Yoji; Xie, Juan; Zhang, Zhijie
This paper investigates the mechanical properties of metal beetle elytron plates (a type of biomimetic sandwich structure) and the elementary unit of the trabecular-honeycomb core structure by compression experiments. The following conclusions are drawn: (1) after reaching the compressive strength, the stress–strain curve of the beetle elytron plate contains a yield plateau that advantageously exploits the material strength of metal and its plastic deformation capacity; (2) the elementary unit of the core structure in beetle elytron plates is proposed explicitly based on the trabecular characteristic; and (3) this elementary unit remains relatively unchanged on the constraint condition of the trabecular structure and has high independence and stability when placed under out-of-plane compression. Thus, the yield plateau and variation tendency of the compressive strength after buckling of this elementary unit are highly consistent with that of the entire structure, which provides the basis for further research on the equivalent parameters and equivalent model of the beetle elytron plate and its trabecular-honeycomb core structure.